The inner structure of pyramid and capital structure: Evidence from China - Kun Su (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
This paper examines the effects of the pyramid inner ownership structure of companies on capital structure in an emerging market economy country. The author uses firm-level panel data of Chinese listed companies to analyze the effects of the inner structure of pyramid on capital structure, and the differences in those effects between regions with different institutional environments. The results indicate that the longer the layers of a pyramid structure, the stronger its "leverage effect", as well as the ultimate owner's motivation to expand debt financing. Thus the layers of pyramid structure have a significantly positive effect on capital structure. However, the chains within a pyramid structure have no significant effect on capital structure. Compared with regions with poor institutional environment, in regions with a better institutional environment the effect of the layers of pyramid structure on capital structure becomes smaller.
Keywords: G32; G38; M48; 330; pyramid ownership structure; institutional environment; capital structure; agency chain